PERUBAHAN PARADIGMA PERAN GURU DALAM PEMBELAJARAN ERA DIGITAL - Angraini, Trisseda; N. Saragi, Lasmaida; Jannah, Miftahul; Sopian, M. (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA, 2017)
The rapid development of science and technology brings us to the digital age with great changes in everything. An age where almost every side of our lives can not be released with digital or electronic devices. The digital age enables us to gain abundant knowledge easily and quickly so that it impacts the paradigm shift in all sides of life. Paradigm change can be interpreted as a change of mindset to the learning process. There are several paradigm shifts that occur such as a paradigm shift to Master. In the digital age, it takes teachers who are able to keep up with the times, can play various roles as bearers of change, learning consultants; which has a high sense of humanity and morals, and social sensitivity, and rational and honest thinking, so as to work well in a dynamic educational environment. This article discusses the paradigm of the digital age teacher in learning that is thought to affect vision, responsibility, social sensitivity, logic ability and teacher honesty. All this leads to the role of teachers in the digital age, namely as agents of change, renewal of knowledge and learning consultants. teachers become the bridge of revolution. By making himself a motivator, which moves students to accessible learning resources.